Reflections on mental health and care technologies - Meola, Maria Elisabete (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
This work's aims to a reflection on concepts and praxis that lay the foundation for the mental health realm, under the Psychiatric Reform movement perspective. Some postulates are stressed. Among them, the primary notion that the look must be aimed to the subject (and not the disease) and his/her position in the field of complexity. It is also stressed that in mental helth the adoption of a transdisciplinary attitude is necessary for the subjefs wholeness apprehension. The manifold kinds of specific knowledge and know-how must articulate to build answers to materialize flexible and complex care structures. These answers ought to involve hearing the patient and offering clinicai and social devices. Occupational Therapy - understood as a care technology - finds in this territory a place for a state-of-art activity: a place for transition and encounter between inside and outside, between inner and outer reality, between thinking and doing, between private and collective.